Determinants of leptospirosis preventive practices among the community in a flood-prone residential area in Kuantan, Malaysia - Mohammad Aidid, Edre; Kadir@Shahar, Hayati; Md Said, Salmiah; Syed Ismail, Sharifah Norkhadijah (Universiti Putra Malaysia, 2018)
Introduction: Leptospirosis is a preventable zoonosis of public health importance. Due to increasing incidence of leptospirosis and seasonal floods affecting Kuantan community, a study was conducted to identify the determinants of leptospirosis preventive practices. Methods: A cross-sectional study was carried out in Perkampungan Sungai Isap, Kuantan, Pahang, Malaysia, which obtained 568 respondents by stratified proportionate random sampling technique. Data was collected using a modified guided questionnaire and analysed using IBM SPSS version 22.0. Results: Majority of the respondents were females (52.6%), Malay ethnicity (98.8%), attended up to secondary school (57.2%), worked in low-risk occupational group (96.0%) and reside in moderate-risk stratum (55.6%). Overall, majority (68%) of the respondents had good knowledge. However, only 38% of the respondents had satisfactory attitude and 18% had satisfactory practice. There were significant associations between stratum and leptospirosis preventive practices (χ2 =11.84, df=2, p=0.003), age group and leptospirosis preventive practices (χ2 =7.41, df=2, p=0.03) and personal income and leptospirosis preventive practices (χ2 =6.32, df=1, p=0.01). Multivariate logistic regression showed that the predictors of satisfactory leptospirosis preventive practices were high-risk stratum (aOR: 3.69, 95% CI: 1.71-8.00, p=0.001) and monthly personal income of less than RM1000 (aOR: 1.65, 95% CI: 1.05-2.59, p=0.03). Conclusions: Leptospirosis can be prevented by having adequate awareness regarding the disease through health promotional activities especially before, during and after flooding, targeting more on those in low to moderate risk areas and higher income group to prevent potential outbreaks.